2021
DOI: 10.1155/2021/6630795
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Protective Mechanism of the Volatile Oil of Acorus tatarinowii against Acute Myocardial Ischemia Injury Using Network Pharmacology and Experimental Validation

Abstract: Acorus tatarinowii is a traditional aromatic resuscitation drug that can be clinically used to prevent cardiovascular diseases. The volatile oil of Acorus tatarinowii (VOA) possesses important medicinal properties, including protection against acute myocardial ischemia (MI) injury. However, the pharmacodynamic material basis and molecular mechanisms underlying this protective effect remain unclear. Using network pharmacology and animal experiments, we studied the mechanisms and pathways implicated in the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Thus, VOA can be used as an auxiliary means for treating and preventing myocardial infarction. Another study ( Zang et al, 2021 ) has shown that the anti-myocardial infarction effect of VOA may be attributed to the inhibition of COX-2 protein apoptosis, the up-regulation of PPAR-α protein regulating energy metabolism, and the activation of VEGF and cAMP signalling pathways. Moreover, based on network pharmacology analysis, the therapeutic effect of VOA on myocardial ischemia may be mediated by COX-2, peroxisome proliferation-activated receptor (PPAR-α), vascular endothelial growth factor (VEGF) and cyclic adenosine monophosphate (cAMP) signalling pathways.…”
Section: Pharmacological Activities and Mechanisms Of Volatile Oil Of...mentioning
confidence: 99%
“…Thus, VOA can be used as an auxiliary means for treating and preventing myocardial infarction. Another study ( Zang et al, 2021 ) has shown that the anti-myocardial infarction effect of VOA may be attributed to the inhibition of COX-2 protein apoptosis, the up-regulation of PPAR-α protein regulating energy metabolism, and the activation of VEGF and cAMP signalling pathways. Moreover, based on network pharmacology analysis, the therapeutic effect of VOA on myocardial ischemia may be mediated by COX-2, peroxisome proliferation-activated receptor (PPAR-α), vascular endothelial growth factor (VEGF) and cyclic adenosine monophosphate (cAMP) signalling pathways.…”
Section: Pharmacological Activities and Mechanisms Of Volatile Oil Of...mentioning
confidence: 99%
“…The GC/IMS system (Flavourspec ® , G.A.S, Dortmund, Germany) was equipped with an autosampler (CTC Analytics AG, Zwingen, There are 18 common components between PTW and KXS, such as β-asarone, trans-2,4-decadien-1-al and methyl eugenol, the main effective substances for antidepressants and tranquilizers. 32 There are 13 common components between PG and KXS, such as γ-elemene and calarene, which are the main active substances. 33 There are 10 common components between PC and KXS, such as β-asarone and isocalamenediol which are the main active substances.…”
Section: Analytical Conditions For Hs-gc/imsmentioning
confidence: 99%
“…The main biologically active ingredients of SCP include flavonoid glycosides, phenylpropane derivatives, amides and lignans [6]. SCP exerts a broad range of pharmacological effects such as protection of PC12 cells from amyloid-beta induced neurotoxicity [7], prevention against cardiovascular diseases [8], as well as increasing the permeability of blood-brain barrier in rats [9]. In this study, we established an in vitro model to investigate the effects of SCP extract on the permeability of BRB and clarify the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%